Performance Analysis of RAW Impact on IEEE 802.11ah Standard affected by Doppler Effect - Marwan, Abdul Aziz; Perdana, Doan; Sanjoyo, Danu Dwi (International journal of computers, communications & control, 2019)
Internet of Things (IOT) offers a new dimension of technology and information where connectivity is available anywhere, anytime, and for any purpose. IEEE 802.11 Wireless Local Area Network group is a standard that developed to answer the needs of wireless communication technology (WI-Fi). Recently, IEEE 802.11 working group released the 802.11ah technology or Wi-Fi HaLow as a Wi-fi standard. This standard works on the 1 GHz frequency band with a broader coverage area, massive device and the energy efficiency issues. This research addresses, the influence of Doppler Effect using Random Waypoint mobility model on 802.11ah with different RAW slot and RAW slot duration are analyzed. The design of the simulation system is done by changing RAW slot and RAW slot duration. Based on the result, it can be concluded that the overall performance of the network with all of the parameter scenarios is decreasing along with the increasing RAW slot, RAW slot duration, and fluctuation. In the RAW slot = 5 scenario with v = 10 km/h has the worst performance with an average delay which is about 0.128225 s, and average throughput is about 0.284337 Mbps while for RAW slot = 1 with an average PDR which is about 99.1076 %. While in the RAW slot duration = 0.020 s scenario with v = 10 km/h has the worst performance with an average delay which is about 0.135581 s, average throughput is about 0.286828 Mbps, and average PDR which is about 99.3165 %.